PKMS Braille Digital Marketing UMKM Al Mumtaz Eduwisata Difabel Penyandang Disabilitas Tunanetra dan Daksa Ringan Era New Normal di Kabupaten Banyuwangi - Adawiyah, Putri Robiatul; Jatmiko, Hadi (Journal of Community Development, 2021)
This PKM aims to solve the problems of Al Mumtaz problems with Disabilities Using Technology Based on Community Inclusion and Disabilities, People with Disabilities who are Blind and Mild Daksa Era of New Normal in Banyuwangi Regency. Braille Digital Marketing Umkm Al Mumtaz Disability Education Using AI Technology Based on Community Inclusion and Disabilities People with Visual and Mild Disabilities Era New Normal in Banyuwangi Regency, aims to overcome the problem of disabilities A / Blind and mild D (1) Lack of Partner knowledge related to Digital Marketing 2) Decrease in consumers using Al Mumtaz Disability Tourism Edu services and Decreased Handicraft Sales during the epidemic period (3) Unavailability of Braille Digital Marketing Module, no media aids that make it easier for A / blind and mild disabilities in marketing innovation for handicraft products ( 4) The lack of access to information and special AI technology media for the blind in terms of improving the quality and marketing of handicraft products. The activities carried out are by holding Braille Digital Marketing training and simulations using the Braille Digital Marketing Module, including training for Braille Digital Marketing workshops using the Braille Module, collaborating with other supporting partners who have computers and braille printers in compiling the Braille Digital Marketing Module, partner assistance ( UMKM Al Mumtaz) in optimizing potential. The resulting output is the increased understanding of the training participants, the Al Mumtaz youtube account of online media publications and print media, dedication articles in the form of national journals, photos and videos of activity documentation, blogs and websites.